Geodetic implications on block formation and geodynamic domains in the South Shetland Islands, Antarctic Peninsula - Berrocoso, M.; Fernández-Ros, A.; Prates, Gonçalo; García, A.; Kraus, S. (Tectonophysics, 2016)
The South Shetland Islands archipelago is dynamically complex due to its tectonic surroundings.Most islands are part of a formerly active volcanic arc, although Deception, Penguin and Bridgeman Islands, aswell as several submarine volcanoes, are characterized by active back-arc volcanism. Geodetic benchmarks were deployed and the movement of the lithosphere to which they were fixed measured to provide geodynamic insight for the South Shetland Islands, Bransfield Basin and Antarctic Peninsula area based on surface deformation. These benchmarks' data add spatial and temporal coverage to previous results. The results reveal two different geodynamic patterns, each confined to a distinct part of the South Shetland Islands archipelago. The inferred absolute horizontal velocity vectors for the benchmarks in the northeastern part of the archipelago are consistent with the opening of the Bransfield Basin, while benchmark vectors in the southwestern part of the archipelago are similar to those of the benchmarks on the Antarctic Peninsula. In between, Snow, Deception and Livingston Islands represent a transition zone. In this area, the horizontal velocity vectors relative to the Antarctic plate shift northeastwards from N toNW. Furthermore, the South Shetland Islands benchmarks, except for that at Gibbs (Elephant) Islands, indicate subsidence, which might be a consequence of the slab roll-back at the South Shetland Trench. In contrast, the uplift revealed by the Antarctic Peninsula benchmarks suggests glacial isostatic adjustment after the Larson Bice-shelf breakup. info:eu-repo/semantics/publishedVersion